Restricted estimators of repeated measurements model for unbalanced data - Abdel-Zahra, Sarah Abbas; AL-Mouel, Abdul Hussein Saber (Journal of statistics & management systems, 2024)
The model of one-way repeated measurements for imbalanced data, as the number of explanations are not the same at some levels, is the subject of this research. We used two methods to estimate the model parameters: the restricted maximum likelihood method and maximum likelihood approach, and we considered some of their characteristics. The Experiment’s practical research goal is to determine how the experimental elements and their interactions affect date palm productivity. The Experiment included the factor of irrigation method with three treatments: drip irrigation, basin irrigation, and the regular tidal method, while the irrigation interval factor included three treatments: 3, 6 and 9 days.